PENENTUAN JENIS FUNGSI BASIS RADIAL DALAM DUAL RECIPROCITY BOUNDARY ELEMENT METHOD - Zahroh, Millatuz (Jurusan Matematika FMIPA Universitas Jember, 2021)
Problems involving modified Helmholtz equation are considered in this paper. To solve the problem numerically, dual reciprocity boundary element method (DRBEM) is employed. Some stage have been passed, using reciprocal relation to approximate boundary integral and domain integral in modified Helmholtz equation . Until, linear equation system are obtained in matrix form. MATLAB is used to calculate the solutions of Solutions of are compared between the exact solution and the numerical solution of modified Helmholtz equation. The numerical results are based on the using of three types of radial basis function to approximate domain integral, such as polinomial, poliharmonik spline and linear types. The solutions show that the polinomial and poliharmonik spline types are more stable and approach to exact solution than linear types.